2009
DOI: 10.1186/1471-230x-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Plastic or metal stents for benign extrahepatic biliary strictures: a systematic review

Abstract: BackgroundBenign biliary strictures may be a consequence of surgical procedures, chronic pancreatitis or iatrogenic injuries to the ampulla. Stents are increasingly being used for this indication, however it is not completely clear which stent type should be preferred.MethodsA systematic review on stent placement for benign extrahepatic biliary strictures was performed after searching PubMed and EMBASE databases. Data were pooled and evaluated for technical success, clinical success and complications.ResultsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 68 publications
0
95
0
5
Order By: Relevance
“…Strictures were subsequently treated by multiple placements of plastic stents (not FCSEMS). Although reports exist suggesting that temporary FCSEMS placement in benign strictures offers a potential alternative to the multiple plastic stent strategy [21,24,27], these findings have been challenged in literature [30]. We treated seven patients with benign biliary strictures using FCSEMS (unpublished data), and we observed complications in six patients.…”
Section: Discussionmentioning
confidence: 92%
“…Strictures were subsequently treated by multiple placements of plastic stents (not FCSEMS). Although reports exist suggesting that temporary FCSEMS placement in benign strictures offers a potential alternative to the multiple plastic stent strategy [21,24,27], these findings have been challenged in literature [30]. We treated seven patients with benign biliary strictures using FCSEMS (unpublished data), and we observed complications in six patients.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, FCSEMS have become commercially available and in some countries they have only received approval for malignant biliary strictures and not to treat BBS. Furthermore, as they have only been introduced in recent years there are few studies on their use compared with several other models of FCSEMS, and an even fewer number of studies comparing their efficacy with plastic stents, which still remain the standard for treatment of BBS [21] . Some studies on PCSEMS or FCSEMS in BBS are shown in Table 3 [22 -28] .…”
Section: Benign Biliary Stricturesmentioning
confidence: 99%
“…9,79 Two systematic reviews showed a 94% success rate with placement of multiple plastic stents, 80% with cSEMS, and 60% with single plastic stents. 9,79 Endoscopic success in stricture resolution for postoperative strictures is around 80% and 20% in chronic pancreatitis strictures. 80 Catalano et al showed that multiple simultaneous plastic stents are superior to single stent placement.…”
Section: Plastic Vs Metal Stentsmentioning
confidence: 99%